The influence of social skills on the subjective perception of quality of life / Influența competențelor sociale asupra percepției subiective a calității vieții - MUSIENCO Natalia (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
This article reflects a brief review of the content of the concepts of quality of life and social skills from the perspective of local authors and from the perspective of foreign literature. We will also present the results of the research on the influence of social skills on the subjective perception of quality of life, conducted in three universities in the Republic of Moldova.